Association between environmental chemicals co-exposure and peripheral blood immune-inflammatory indicators - Liu, Yong; Zhang, Zhihui; Han, Dongran; Zhao, Yiding; Yan, Xiaoning; Cui, Shengnan (Frontiers in Public Health, 2022)
Chronic inflammation is closely related to chronic inflammatory diseases, autoimmune diseases and cancer. Few studies have evaluated the effects of exposure to multiple chemical combinations on immunoinflammatory related biomarkers and their possible molecular mechanisms. This study explored the effect of exposure to various chemicals on immune inflammatory biomarkers and its molecular mechanism. Using data from 1,723 participants in the National Health and Nutrition Examination Survey (NHANES, 2011-2012), the aim was to determine the association between chemical mixtures and immunoinflammatory biomarkers (including White blood cell (Wbc), neutrophil (Neu), lymphocytes (Lym) and Neutrophil-to-lymphocyte ratio (NLR)) using linear regression model, weighted quantile sum regression (WQSR) model, and bayesian nuclear machine regression (BKMR) model. Meanwhile, functional enrichment analysis and protein–protein interaction network establishment were performed to explore the molecular mechanism of inflammation induced by high-weight chemicals. In the linear regression model established for each single chemical, the four immunoinflammatory biomarkers were positively correlated with polycyclic aromatic hydrocarbons (PAHs), negatively correlated with perfluoroalkyl substances (PFASs), and positively or negatively correlated with metallic and nonmetallic elements. WQSR model showed that cadmium (Cd), perfluorooctane sulfonic acid (PFOS) and perfluorodecanoic acid (PFDE) had the highest weights. In BKMR analysis, the overall effect of chemical mixtures was significantly associated with Lym and showed an increasing trend. The hub genes in high-weight chemicals inflammation-related genes were interleukin-6 (IL6), tumor necrosis factor (TNF) and interleukin-1B (IL1B), etc. They were mainly enriched in Inflammatory response, Cytokine-cytokine receptor interaction, Th17 cell differentiation and IL-17 signaling pathway. The above results show that exposure to environmental chemical cocktails primarily promotes an increase in Lym across the immune-inflammatory spectrum. The mechanism leading to the inflammatory response may be related to the activation of IL-6 amplifier by the combined exposure of environmental chemicals.